El lugar del texto en la Teología de la Liberación: Aportes a la hermenéutica bíblica - Carbullanca Núñez, César (Estudios eclesiásticos, 2023)
The article analyzes and discusses the epistemological status of the place of the text in Liberation Theology (TdL). The ambiguities, simplifications, biases verified by multiple authors lie in an instrumental vision of language that disconnects the concepts of text and place. Therefore, we analyze the concepts of text and place referring to both history and the biblical text. In view of this, we first place in perspective the development of the problems, knots, ambiguities, and juxtapositions in these concepts used by the authors as well as by various groups of Christians. Subsequently, we carry out a critical reflection analyzing and questioning the critical points of these concepts used by TdL, trying to give semiotic clues that help to overcome and promote an integral theory of the text in biblical and theological work in Latin America. In this way, these semiotic reflections intend to show that the epistemic relevance of the voice of the poor in the Hermeneutics of Liberation (HdL) continues to be a current challenge that must be reflected on and continued, in order to promote a new generation of Biblical studies at the service of liberation on the Continent.